Practical Electrical Engineering - N. Makarov, Sergey; Ludwig, Reinhold; Bitar, Stephen J.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This textbook provides comprehensive, in-depth coverage of the fundamental concepts of electrical and computer engineering. It is written from an engineering perspective, with special emphasis on circuit functionality and applications. Reliance on higher-level mathematics and physics, or theoretical proofs has been intentionally limited in order to prioritize the practical aspects of electrical engineering. This text is therefore suitable for a number of introductory circuit courses for other majors such as robotics, mechanical, biomedical, aerospace, civil, architecture, petroleum, and industrial engineering. The authors' primary goal is to teach the aspiring engineering student all fundamental tools needed to understand, analyze and design a wide range of practical circuits and systems. Their secondary goal is to provide a comprehensive reference, for both major and non-major students as well as practicing engineers. Provides a self-contained, fundamental textbook on electric circuits and basic electronics, designed to be accessible to students from a variety of engineering disciplines; Helps students to bridge their academic and industrial careers, including for example, answers to typical interview questions for an entry-level position in electrical engineering and circuit design; Includes over 1,500 figures, about 1,200 homework problems, and comprehensive summaries at the end of every chapter.
From Physics to Electric Circuits -- Major Circuit Elements -- Circuit Laws and Networking Theorems -- Circuit Analysis and Power Transfer -- Operational Amplifier and Amplifier Models -- Dynamic Circuit Elements -- Transient Circuit Fundamentals -- Steady-State AC Circuit Fundamentals -- Filter Circuits. Frequency Response, Bode Plots, and Fourier Transform -- Second-Order RLC Circuits -- AC Power and Power Distribution -- Electric Transformer and Coupled Inductors -- Switching Circuits -- Analog to Digital Conversion -- Embedded Computing -- Electronic Diode and Diode Circuits -- Bipolar Junction Transistor and BJT Circuits -- MOS Field Effect Transistor (MOSFET).
Keywords: Electronic circuits; Electronics; Electronic Circuits and Systems; Electronics and Microelectronics, Instrumentation